The Effect of Adding a Square Disturbance on the Flow Characteristics across Circular Cylinders Arranged in Tandem - Riani, Novi Indah; Lostari, Aini; Ulum, Miftahul; Hakim, Ainul (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
Circular cylinder is one form of bluff body that is often used in engineering and industrial applications. The addition of a square placed in front of the circular cylinder aims to accelerate the flow from laminar to turbulent so that flow separation can be delayed more slowly so that the resulting pressure drag is smaller. The research method used was experimental using two circular cylinders arranged in tandem with a diameter (D) of 25 mm and variations in the distance between cylinders (L/D) 2;2,5;3;3,5;4 and two square-shaped square bodies (SDB) in front of each cylinder with dimensions of 4 mm. Position of SDB angle is 30o and the gap distance is 0.4 mm. The Reynolds number used is 2.3x104. This study aims to obtain the distribution of pressure coefficient (CP), drag pressure coefficient (CDP) and velocity profile behind the test specimen. The results showed that the addition of two square-shaped square bodies on each cylinder can reduce the drag force on the cylinder which causes a difference in values, where the largest pressure coefficient value occurs at a distance of L/D 4 with a value of -1.073 and the lowest value of drag pressure coefficient (CDP) at a distance of L/D 2 on the upstream cylinder with a value of 0.0786. While the downstream cylinder is located at a distance of L/D 3 with a value of -0.079 and the lowest speed value is located in the variation of L/D 4 with a value of 9.52 m/s.